Efetividade in vitro de agentes irrigantes na neutralização de endotoxinas em canais radiculares - Oliveira, Luciane Dias de [UNESP] (2005)
The purpose was to evaluate the effects of sodium hypochlorite, chiorhexidine, calcium hydroxide and polymyxin B on endotoxins in root canals. Ninety eigth freshly extracted maxillary incisors were used in this study. The crowns of teeth were sectioned near the CEJ in order to standardize the root length to 14 mm. The specimens were sterilized with 60Co gamma irradiation and standardized suspension containing Escherichia coli endotoxin was inoculated into the 84 root canals. After 24 h, the root canals were instrumented to an apical size #80 file and were randomly assigned to seven 7 groups (n=14), according to the irrigant used: G1) NaOCJ 2,5%; G2) NaOCJ 5,25%; G3) chiomexidine; G4) calcium hydroxide; G5) polymyxin B; G6) positive control; G5) negative control. Two collections of the content of the canal root were accomplished to verify endotoxin detoxification, a soon after the instrumentation (collect immediate) and other after seven days (second collect). The detoxification of endotoxin was evaluated by Limulus lysate assay and antibody production in B-lymphocytes culture. The resulls obtained in the Limulus were submitted to the statistical analysis (Kuskall-Wallis and Dunn) and obtained in the praduction of antibodies were analyzed by ANOVA and test of Tukey (5%). ln the collect immediate, the groups G1 (NaOCI 2,5%), G2 (NaOC/5,25%) and G3 (chiorhexidine) didn't endotoxin detoxify, being statistically similar to G6 (positive control) (p>0,05), while the groups G4 (Ca(OHJ2 O, 14%) e G5 (polymyxin B) demonstrated effectiveness on LPS, with resulted statistically similar to G7 (control negative) (p>0,05) and different from the other groups (p <0,05). ln the collect alter seven days, presence of LPS was detected in the groups G4 and G5, being significantly smaller to the groups G1, G2 and G3. Like this, it could be concluded that only the solutions of Ca(OH)2 and polymyxin B significantly....